Island Operations of Parallel Synchronous Generators - Simulators Case Study for Large Power Plants. Issue 27 (2016) - Neuman, P.
Abstract: While increasing integration of renewable energy sources (RES), which are unregulated and difficult to predict, a large system of nuclear power plants must provide balancing peaks in the production of renewable energy. It is also important to simulate the rapid changes in the power of individual NPP units, and for these regimes to train operators of nuclear units. Therefore the paper is aimed to Island Operations of More Parallel Electric Synchronous Generators Connected to One Substation of Power Grid. For the control of rapid and poorly predicted power peaks / deviations it is also necessary to use large Nuclear Power Plants. These control requirements are not yet required to NPP and therefore NPP Simulators can not be used for these purposes. Firstly, there are described the results of the Case Study: Engineering and Training Simulators for Large Conventional and Nuclear Power Plants. Initially there are presented the simulations of different island operations of power plant turbine generators connected to one substation into the power grid on the example of the Power and Heating Plant with six parallel operating synchronous generators. Generally the Power/Performance K-Factor (KF) are defined for the T&D Systems. K-Factor characterizes the electrical properties of the systems. On the simulator the instructor chosen size distribution system (i.e., KF) in which generators are electrically connected. For different island operations (whose electrical "hardness" depends on the size of KF) will be shown the results of the simulations on the Dispatcher Training Simulator (DTS) used for the training of parallel operations of two or more power turbine generators / blocks. The simulation models are created in MATLAB - SIMULINK. Secondly, a similar multi-block island mode will be also analyzed for a large Nuclear Power Plants.